Pengukuran Kualitas Pelayanan Rumah Sakit di Aceh dengan Model HSQ-Metrix - Iwan Budhiarta; Muttaqin Samuthi (Universitas Proklamasi 45 Yogyakarta, 2019)
From the preliminary study, the results stated that there was a tendency for an increase in healthcare tourism of Acehnese visits to Malaysia from year to year. The chaotic condition represent of the quality of health services in Indonesia, especially in Aceh, that must be sought for the best solution. Therefore research was carried out with the title